Welcome to Westonci.ca, where curiosity meets expertise. Ask any question and receive fast, accurate answers from our knowledgeable community. Discover in-depth solutions to your questions from a wide range of experts on our user-friendly Q&A platform. Get precise and detailed answers to your questions from a knowledgeable community of experts on our Q&A platform.
Sagot :
To address the question of which statement must be true given [tex]\(x \Rightarrow y\)[/tex] and [tex]\(y \Rightarrow z\)[/tex], we need to employ the transitive property of implications in logical reasoning. Let’s break it down step-by-step.
### Step-by-Step Solution:
1. Understand the Definitions and Premises:
- The implication [tex]\(x \Rightarrow y\)[/tex] means that if [tex]\(x\)[/tex] is true, then [tex]\(y\)[/tex] must also be true.
- Similarly, [tex]\(y \Rightarrow z\)[/tex] means that if [tex]\(y\)[/tex] is true, then [tex]\(z\)[/tex] must also be true.
2. Apply the Transitive Property:
- The transitive property in logic states that if [tex]\(A \Rightarrow B\)[/tex] and [tex]\(B \Rightarrow C\)[/tex], then [tex]\(A \Rightarrow C\)[/tex].
- Here, if we take [tex]\(x \Rightarrow y\)[/tex] as [tex]\(A \Rightarrow B\)[/tex] and [tex]\(y \Rightarrow z\)[/tex] as [tex]\(B \Rightarrow C\)[/tex], we can chain these implications together.
3. Chain the Implications:
- From [tex]\(x \Rightarrow y\)[/tex], we have that if [tex]\(x\)[/tex] is true, then [tex]\(y\)[/tex] is true.
- From [tex]\(y \Rightarrow z\)[/tex], we have that if [tex]\(y\)[/tex] is true, then [tex]\(z\)[/tex] is true.
- Combining these, if [tex]\(x\)[/tex] is true, then [tex]\(y\)[/tex] is true, and if [tex]\(y\)[/tex] is true, then [tex]\(z\)[/tex] is true. Therefore, if [tex]\(x\)[/tex] is true, [tex]\(z\)[/tex] must also be true.
4. Conclusion:
- Therefore, the combined implication gives us [tex]\(x \Rightarrow z\)[/tex].
Since [tex]\(x \Rightarrow z\)[/tex] must be true, the correct statement is:
[tex]\( \boxed{4} \)[/tex] or D. [tex]\( x \Rightarrow z \)[/tex]
### Step-by-Step Solution:
1. Understand the Definitions and Premises:
- The implication [tex]\(x \Rightarrow y\)[/tex] means that if [tex]\(x\)[/tex] is true, then [tex]\(y\)[/tex] must also be true.
- Similarly, [tex]\(y \Rightarrow z\)[/tex] means that if [tex]\(y\)[/tex] is true, then [tex]\(z\)[/tex] must also be true.
2. Apply the Transitive Property:
- The transitive property in logic states that if [tex]\(A \Rightarrow B\)[/tex] and [tex]\(B \Rightarrow C\)[/tex], then [tex]\(A \Rightarrow C\)[/tex].
- Here, if we take [tex]\(x \Rightarrow y\)[/tex] as [tex]\(A \Rightarrow B\)[/tex] and [tex]\(y \Rightarrow z\)[/tex] as [tex]\(B \Rightarrow C\)[/tex], we can chain these implications together.
3. Chain the Implications:
- From [tex]\(x \Rightarrow y\)[/tex], we have that if [tex]\(x\)[/tex] is true, then [tex]\(y\)[/tex] is true.
- From [tex]\(y \Rightarrow z\)[/tex], we have that if [tex]\(y\)[/tex] is true, then [tex]\(z\)[/tex] is true.
- Combining these, if [tex]\(x\)[/tex] is true, then [tex]\(y\)[/tex] is true, and if [tex]\(y\)[/tex] is true, then [tex]\(z\)[/tex] is true. Therefore, if [tex]\(x\)[/tex] is true, [tex]\(z\)[/tex] must also be true.
4. Conclusion:
- Therefore, the combined implication gives us [tex]\(x \Rightarrow z\)[/tex].
Since [tex]\(x \Rightarrow z\)[/tex] must be true, the correct statement is:
[tex]\( \boxed{4} \)[/tex] or D. [tex]\( x \Rightarrow z \)[/tex]
We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. Discover more at Westonci.ca. Return for the latest expert answers and updates on various topics.